A Pengenalan Literasi Anti Korupsi bagi Siswa SD Negeri 1 Sumber Mulyo, Kecamatan Sumber Rejo, Kabupaten Tanggamus - Fatahillahi, Ahmad Hadi; Savitri, Eka; Arjuna, Guruh Fajri; Syah, Tansri Adzlan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Effective Anti-Corruption Education Can Shape Students' Character and Attitudes to Understand and Reject Corruption in the Future. Schools as educational institutions play an important role in the process of forming students' character. This study aims to explore the implementation of the introduction of anti-corruption literacy at SD Negeri 1 Sumber Mulyo, Sumber Rejo District, Tanggamus Regency. The method used is observation at SDN 1 Sumber Mulyo and students in grades 5 and 6 became participants in the socialization activities. The purpose of the approach and observation carried out is to get to know the conditions and behavior of students at school better. The anti-corruption literacy program implemented at SD Negeri 1 Sumber Mulyo has succeeded in increasing students' awareness of the importance of honesty and integrity in everyday life. Through interactive and easy-to-understand methods, students can understand the forms of corrupt behavior that often occur on a small scale but have a big impact if left unchecked.